Oxygen therapy in COPD and interstitial lung disease: navigating the knowns and unknowns. Issue 3 (16th September 2019) - Khor, Yet H.; Renzoni, Elisabetta A.; Visca, Dina; McDonald, Christine F.; Goh, Nicole S. L.
Domiciliary oxygen therapy is often prescribed for patients with hypoxaemia due to advanced lung disease, most commonly chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD). Long-term oxygen therapy (LTOT) trials conducted in patients with COPD in the 1980s remain the basis for clinical decisions and guideline recommendations regarding LTOT for patients with non-COPD conditions as there is a lack of high-quality evidence concerning its use in the non-COPD population. There is also a lack of evidence for the use of ambulatory and nocturnal oxygen therapy in patients with isolated exertional and nocturnal hypoxaemia. These deficiencies pose significant challenges in patient care, with consequent discrepancies in guideline recommendations and clinical approaches. In recent years, new studies have been and are currently being conducted to fill the gaps in our understanding and use of domiciliary oxygen therapy for other indications, including ILD. This article provides a comparison of the epidemiology and significance of hypoxaemia in patients with COPD and ILD, with an up-to-date review of current evidence regarding the role of different types of domiciliary oxygen therapy in these conditions. Despite the significance of hypoxaemia in patients with chronic lung diseases, an up-to-date review shows current evidence for clinical use of domiciliary oxygen therapy remains limited http://bit.ly/33aW31n